2020
DOI: 10.3892/etm.2020.8420
|View full text |Cite
|
Sign up to set email alerts
|

Th2 cells as an intermediate for the differentiation of na�ve T cells into Th9 cells, associated with the Smad3/Smad4 and IRF4 pathway

Abstract: Type 9 T-helper (Th9) cells are associated with atopic and inflammatory diseases. Their increased levels and functions contribute to a number of inflammatory disorders, where they are accompanied by enhanced Th2-cell activity. However, there is currently no consensus regarding the association between Th9 and Th2 cells. Th9 cells may be induced from naïve T (Th0) cells under specific polarization conditions in vitro, a process driven by the addition of specific cytokines. In the present study, Th0 cells were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Its receptor is expressed on sensory neurons, epithelial cells or keratinocytes 88,89 . Th2 immune responses are often accompanied by allergen‐specific Th9 cells, which differentiate upon exposure to IL‐4 and TGF‐β 90 . Th9 cells can be considered substantial players in type IVb hypersensitivity.…”
Section: Mechanisms Of the Most Important Allergic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its receptor is expressed on sensory neurons, epithelial cells or keratinocytes 88,89 . Th2 immune responses are often accompanied by allergen‐specific Th9 cells, which differentiate upon exposure to IL‐4 and TGF‐β 90 . Th9 cells can be considered substantial players in type IVb hypersensitivity.…”
Section: Mechanisms Of the Most Important Allergic Diseasesmentioning
confidence: 99%
“…88,89 Th2 immune responses are often accompanied by allergen-specific Th9 cells, which differentiate upon exposure to IL-4 and TGF-β. 90 Th9 cells can be considered substantial players in type IVb hypersensitivity. They produce IL-9, which enhances IL-4-mediated synthesis of IgE by B cells and is an important growth factor for MC precursors in the bone marrow, eosinophils and basophils.…”
Section: F I G U R Ementioning
confidence: 99%
“…For example, TGF-β activates Foxp3, resulting in Th0-to-Treg cell differentiation ( 44 ). TGF-β also promotes Th0 -to-Th9 differentiation by inducing PU.1, which is encoded by Sfpi1 ( 26 ), as well as IRF4, activated by IL-4 ( 27 ). BATF is another TF necessary for Th9 cell differentiation ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…PU.1 and IRF4 have proven critical for Th9 cell differentiation ( 24 , 25 ). PU.1 is induced by TGF-β ( 26 ), while IRF4 is induced by IL-4 ( 27 ) in conjunction with antigen receptor stimulation. Furthermore, the ectopic expression of PU.1 or IRF4 increases IL-9 production in the polarization of Th9 cell cultures ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increased levels and functions of type 9 T-helper (Th9) cells involved in inflammatory disease, accompanied with increased Th2-cell activity. 89 Further study indicated that SMAD4 was involved in Th2 differentiated into Th9 through TGF-b/SMAD3/SMAD4 and interferon-regulatory factor4 (IRF-4) signaling pathway and loss expression of SMAD4 lead to Th2-related cytokines, such as IL-4 and IL-13, and serum IgA over-production, which was associated with the pathogenesis of human IgA nephropathy. 89 , 90 …”
Section: Functions Of Smad4 and Its Mutants In T Cellsmentioning
confidence: 98%